Marketing of Universities of Technology: examining the relationships between market orientation elements, barriers and University performance - Mokoena, Bakae Aubrey (My University, 2015)
The marketing concept is posited as the philosophical foundation of the marketing disciplines and market orientation invariably refer to the operationalisation of the marketing concept into a management orientation. Engaging in marketing activities may be important but market orientation is a vital ingredient in determining an institutional success, despite inherent barriers towards its successful implementation. A higher education institution (HEI) can be market oriented only if it understand its market. This study was conducted with the main objective of seeking to establish Universities of Technology (UoTs) implementation levels of market orientation, possible barriers to market orientation and their influence on university performance. A non-probability sampling method (convenience sampling) was used in the study. The sampling frame for the study included full-time employed academics in all six UoTs in South Africa. Pre-testing and a pilot study preceded the main survey and reliabilities were measured using the Cronbach alpha coefficients. Out of 1250 questionnaires sent to participating institutions, a total of 528 responses were received and this resulted in a return rate of 42.24% for the main study. The statistical analysis of the collected data included exploratory factor analysis, descriptive statistical analysis, correlation analysis, confirmatory factor analysis and structural equation modelling to test the posited hypotheses. The findings of the study supported the predetermined theoretical and the empirical objectives as well as the hypotheses of the study. The findings further indicated that the market orientation of UOTs in South Africa was determined by seven fundamental factors within the institutions being market intelligence generation, interfunctional coordination, customer orientation, market intelligence dissemination, intelligence response design, intelligence response implementation and interdepartmental dynamics. Furthermore, three key barriers to market orientation were identified, namely internal, external and organisational environmental factors. In addition, the study also found a significant impact of market orientation on university performance as consistent with previous market orientation studies undertaken in other contexts. Recommendations emanating from the study will address various concerns on effective incorporation of the market orientation paradigm. Commitment and communication from top management to all units to support market orientation is critical. The support of those making strategic decisions is needed to garner the necessary support of other employees in UoTs, especially top and senior management buy-in and support. Marketing information generation should be a starting point when developing or adapting marketing strategies. HEIs should realise that marketing information dissemination is an effective way to reach prospective students and to create credible and persuasive communication channels. The development of a marketing strategy should also involve the inter-functional coordination and interdepartmental dynamics that enables HEIs to meet students’ needs and enhance service delivery to all its stakeholders. Key aspects that need to be prioritised includes: establishment of structures for marketing coordination, marketing efforts to be driven by teams to bring about synergy and cross fertilisation of ideas across departments and marshalling of resources in order to improve performance of all business units. Managers in different HEIs can also enhances performance of their instituions by implementing these key recommendations. This study will significantly contribute to the critical challenge facing HEIs, being to create the combination of the culture and the climate that maximises organisational learning, resources and capabilities to create superior university performance that is prescribed by the Department of Higher Education and Training (DoHET). Other HEIs could learn from this study and utilise the research to diagnose and remedy barriers within their operational spheres.
Keywords: Higher Education Institutions; Market orientation; South African higher education; Universities of Technology; 378.101; Education, Higher -- Marketing